2018
DOI: 10.1070/rcr4792
|View full text |Cite
|
Sign up to set email alerts
|

Azoloazines as A2a receptor antagonists. Structure – activity relationship

Abstract: Non-xanthine inhibitors of the adenosine A2a receptor of the azoloazine series are good candidates for use as drugs for the treatment of neurodegenerative diseases and sepsis. This review systematizes and summarizes the structure – activity relationships in the series of triazoloazines, including annulated pyrimidines, pyrazines and triazines, as well as their tricyclic fused analogues. The above relationships for such systems are analyzed. The structures of the most efficient functional moieties from the poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 67 publications
0
11
0
1
Order By: Relevance
“…It was shown previously that nitrogroup plays essential role in the azoloazine series for pronounced antiviral/antiseptic effect [7]. Considering this and structural similarity between nitro and ethoxycarbonyl fragments we synthesized a series of a new azolo[1,5a]pyrimidines 3a-l by the reaction of commercially available aminoazoles 1a-h and carbonyl-containing synthetic equivalents e.g.…”
Section: Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown previously that nitrogroup plays essential role in the azoloazine series for pronounced antiviral/antiseptic effect [7]. Considering this and structural similarity between nitro and ethoxycarbonyl fragments we synthesized a series of a new azolo[1,5a]pyrimidines 3a-l by the reaction of commercially available aminoazoles 1a-h and carbonyl-containing synthetic equivalents e.g.…”
Section: Chemistrymentioning
confidence: 99%
“…At the same time, heterocyclic derivatives of the azoloazine nature and their condensed derivatives are known for their broad range of biological activity [7]. Especially, it was shown that these compounds have a pronounced protective effect against septic shock and influenza virus in vivo [7,8]. Consequently, we consider the study of azoloazine heterocycles as potential anticoagulant agents for the treatment of cytokine storm and, in particular, DIC promising and very relevant in the modern epidemic situation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…В классе веществ, производных нитроазолоазинов, имеются соединения с разнообразной биологической активностью [19], в числе которой противовирусное [3, 10] и аденозинергическое действия [22], предотвращение септического шока [23]…”
Section: выпуск 1 (69) 2019unclassified
“…It is well known that derivatives of 1,2,4triazine-3-thione exhibit pesticide activity [1], as well as anticancer [2], psychotropic [3], and antiviral activity [4]. Annelated derivatives of triazines offer prom-ise in the field of drug development [5][6][7][8][9], in particular for neurodegenerative diseases [10]. Besides, 3-methylsulfanyl-1,2,4-triazine has been used as a base for oligomers with optoelectronic properties [11].…”
Section: Introductionmentioning
confidence: 99%